Probing charge-transfer processes in Pt/TiO 2 photocatalysts by amperometric/potentiometric photo-SECM - Tianyu Bo; Haoqing Su; Ziyuan Wang; Je Hyun Bae; Gaukhar Askarova; Shu Hu; Michael V. Mirkin (Proceedings of the National Academy of Sciences, 2026)
Electrocatalysts in combination with photoelectrodes can provide higher activity and/or lower overpotential for a broad range of photoelectrochemical processes. Although cocatalyst nanoparticles (NPs) on semiconductor surfaces have been extensively studied, spatially resolved kinetic measurements of charge-transfer processes in such systems remain challenging. Here, we introduce a unique approach based on a single setup employing contact amperometric/potentiometric photo-scanning electrochemical microscopy for quantitative, high-resolution measurements of photoelectrochemical processes in nanostructured photocatalysts. Amperometric SECM experiments are coupled with nanoscale local potential measurements made using the same nanotip, which is brought within the tunneling distance from the sample surface. Pt NPs electrodeposited on the surface of Nb-doped TiO 2 rutile (110) single crystals are used as a model experimental system to demonstrate the capabilities of the developed technique for probing local rates of photogenerated hole/electron transfers, such as overall water splitting (OWS) with coevolved H 2 and O 2 , as well as the oxidation/reduction of a reversible redox mediator (e.g., ferro/ferricyanide). This methodology resolves spatial variations in photocatalytic reactivity of nanoscale cocatalysts supported on semiconductors with a spatial resolution on the order of 10 nm. In the Pt/Nb:TiO2 system, this method identifies distinct cathodic and anodic sites separated by ~150 nm, with local surface potentials of approximately −0.53 V and +0.58 V vs. Ag/AgCl, respectively. Complementary structural/compositional and spectroscopic analyses reveal the coexistence of metallic Pt and oxidized Pt species under OWS conditions, establishing asymmetric surface energetics consistent with a ~1.5 eV difference in local band-edge position and thereby driving directional carrier separation within Nb:TiO 2 .